The Influence of Bcl-3 Expression on Cell Migration and Chemosensitivity of Gastric Cancer Cells via Regulating Hypoxia-Induced Protective Autophagy - Hu, Lin (J Gastric Cancer, 2020)
PURPOSE: Gastric cancer is a highly metastatic malignant tumor, often characterized by chemoresistance and high mortality. In the present study, we aimed to investigate the role of B-cell lymphoma 3 (Bcl-3) protein on cell migration and chemosensitivity of gastric cancer. MATERIALS AND METHODS: The gastric cancer cell lines, AGS and NCI-N87, were used for the in vitro studies and the in vivo studies were performed using BALB/c nude mice. Western blotting, wound healing assay, Cell Counting Kit-8 assay, immunohistochemistry, and terminal deoxynucleotidyl transferase dUTP nick end labeling assay were used to evaluate the role of Bcl-3 in gastric cancer. RESULTS: We found that the protein expression of hypoxia (HYP)-inducible factor-1α and Bcl-3 were markedly upregulated under hypoxic conditions in both AGS and NCI-N87 cells in a time-dependent manner. Interestingly, small interfering RNA-mediated knockdown of Bcl-3 expression affected the migration and chemosensitivity of the gastric cancer cells. AGS and NCI-N87 cells transfected with si-RNA-Bcl-3 (si-Bcl-3) showed significantly reduced migratory ability and increased chemosensitivity to oxaliplatin, 5-fluorouracil, and irinotecan. In addition, si-Bcl-3 restored the autophagy induced by HYP. Further, the protective role of si-Bcl-3 on the gastric cancer cells could be reversed by the autophagy inducer, rapamycin. Importantly, the in vivo xenograft tumor experiments showed similar results. CONCLUSIONS: Our present study reveals that Bcl-3 knockdown inhibits cell migration and chemoresistance of gastric cancer cells through restoring HYP-induced autophagy.